Effects of rhBMP-2 on Sandblasted and Acid Etched Titanium Implant Surfaces on Bone Regeneration and Osseointegration: Spilt-Mouth Designed Pilot Study - Kim, Nam-Ho (Biomed Res Int, 2015)
This study was conducted to evaluate effects of rhBMP-2 applied at different concentrations to sandblasted and acid etched (SLA) implants on osseointegration and bone regeneration in a bone defect of beagle dogs as pilot study using split-mouth design. Methods. For experimental groups, SLA implants were coated with different concentrations of rhBMP-2 (0.1, 0.5, and 1 mg/mL). After assessment of surface characteristics and rhBMP-2 releasing profile, the experimental groups and untreated control groups (n = 6 in each group, two animals in each group) were placed in split-mouth designed animal models with buccal open defect. At 8 weeks after implant placement, implant stability quotients (ISQ) values were recorded and vertical bone height (VBH, mm), bone-to-implant contact ratio (BIC, %), and bone volume (BV, %) in the upper 3 mm defect areas were measured. Results. The ISQ values were highest in the 1.0 group. Mean values of VBH (mm), BIC (%), and BV (%) were greater in the 0.5 mg/mL and 1.0 mg/mL groups than those in 0.1 and control groups in buccal defect areas. Conclusion. In the open defect area surrounding the SLA implant, coating with 0.5 and 1.0 mg/mL concentrations of rhBMP-2 was more effective, compared with untreated group, in promoting bone regeneration and osseointegration.